Analysis of Selected Approaches to the Integral Pedagogy in Polish Pedagogical Thought - Lucyna Dziaczkowska (Nicolaus Copernicus University in Toruń, 2018)
The article presented has attempted to analyse the selected approaches to integral pedagogy in Polish pedagogical thought. The rationale for the choices made by the author were personal declarations of practice, such as a type of pedagogy by specific researchers and/or classifying them as integral pedagogues by other pedagogues. The author provides arguments that the idea of integrity in pedagogy concerns researchers representing various trends in pedagogical thinking. At the same time, it is a subject of disputes conducted by them. The presentation of selected approaches of integral pedagogy by Sergiusz Hessen, Stefan Kunowski, Irena Wojnar, Bogdan Suchodolski, Marian Nowak, Zbigniew Kwieciński and Monika Jaworska-Witkowska, ends with a brief description of the position of Wiesław Andrukowicz, which is polemical towards their work.